2019
DOI: 10.1093/ibd/izz092
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Incidence of Inflammatory Bowel Disease in Different Age Groups in the United States

Abstract: Abstract Background Data on the incidence of inflammatory bowel disease (IBD) by age group are available in countries outside of the United States or localized populations within the United States. We aimed to estimate the incidence rates (IRs) of IBD by age group using a US multiregional data set. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 28 publications
0
19
1
1
Order By: Relevance
“…First, the low incidence values in young children over time do not resemble those of recent studies, including a meta-analysis that reported an increasing trend of IBD incidence in this age category in the Western world (24,25). On the other hand, incidence reports from the United Kingdom and the United States presented similar age distributions as those observed in this study (26,27). These results might suggest that IBD onset occurs more often after childhood among the Portuguese population.…”
Section: Discussioncontrasting
confidence: 87%
“…First, the low incidence values in young children over time do not resemble those of recent studies, including a meta-analysis that reported an increasing trend of IBD incidence in this age category in the Western world (24,25). On the other hand, incidence reports from the United Kingdom and the United States presented similar age distributions as those observed in this study (26,27). These results might suggest that IBD onset occurs more often after childhood among the Portuguese population.…”
Section: Discussioncontrasting
confidence: 87%
“…Dysregulation of MGB axis by endogenous and exogenous factors, such as aging and social defeat, accelerates the occurrence of psychiatric disorders such as depression, anxiety, autism, and AD [31,32]. Aging accelerates the incidence of neurodegenerative disorders and gut dysbiosis, which causes inflammatory bowel disease (IBD) [33,34]. Patients with IBD display cognitive impairments and psychomotor performance, particularly during the active stage of the disease [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with multiple studies which have similarly documented increasing hospitalizations in PIBD. 12,[25][26][27][28] However, some studies have reported stable or decreasing incidence of IBD in North America. 29,30 It is clear from these conflicting data, that overall trends in incidence and prevalence of IBD in the United States are not clearly established.…”
Section: Discussionmentioning
confidence: 99%